Jóhann Páll Árnason, Austur, vestur og aftur heim: Greinar um samfélagsheimspeki og siðmenningargreiningu (Hið íslenska bókmenntafélag, 2024) - Guðmundur Ævar Oddsson (Nordicum-Mediterraneum)
East, West, and Home Again[1] Sociologist and philosopher Jóhann Páll Árnason, professor emeritus at La Trobe University in Melbourne, is one of Iceland’s most important academics and theorists ever in the humanities and social science.